Progress towards the UNAIDS 90-90-90 goals by age and gender in a rural area of KwaZulu-Natal, South Africa: a household-based community cross-sectional survey - Helena Huerga; Gilles Van Cutsem; Jihane Ben Farhat; Adrian Puren; Malika Bouhenia; Lubbe Wiesner; Linda Dlamini; David Maman; Tom Ellman; Jean-François Etard (BMC, 2018)
Abstract Background The Joint United Nations Programme on HIV/AIDS (UNAIDS) has developed an ambitious strategy to end the AIDS epidemic. After eight years of antiretroviral therapy (ART) program we assessed progress towards the UNAIDS 90-90-90 targets in Mbongolwane and Eshowe, KwaZulu-Natal, South Africa. Methods We conducted a cross-sectional household-based community survey using a two-stage stratified cluster probability sampling strategy. Persons aged 15-59 years were eligible. We used face-to-face interviewer-administered questionnaires to collect information on history of HIV testing and care. Rapid HIV testing was performed on site and venous blood specimens collected from HIV-positive participants for antiretroviral drug presence test, CD4 count and viral load. At the time of the survey the CD4 threshold for ART initiation was 350 cells/μL. We calculated progression towards the 90-90-90 UNAIDS targets by estimating three proportions: HIV positive individuals who knew their status (first 90), those diagnosed who were on ART (second 90), and those on ART who were virally suppressed (third 90). Results We included 5649/6688 (84.5%) individuals. Median age was 26 years (IQR: 19-40), 62.3% were women. HIV prevalence was 25.2% (95% CI: 23.6-26.9): 30.9% (95% CI: 29.0-32.9) in women; 15.9% (95% CI: 14.0-18.0) in men. Overall progress towards the 90-90-90 targets was as follows: 76.4% (95% CI: 74.1-78.6) knew their status, 69.9% (95% CI: 67.0-72.7) of those who knew their status were on ART and 93.1% (95% CI: 91.0-94.8) of those on ART were virally suppressed. By sex, progress towards the 90-90-90 targets was: 79%-71%-93% among women; and 68%-68%-92% among men (p-values of women and men comparisons were < 0.001, 0.443 and 0.584 respectively). By age, progress was: 83%-75%-95% among individuals aged 30-59 years and 64%-58%-89% among those aged 15-29 years (p-values of age groups comparisons were < 0.001, < 0.001 and 0.011 respectively). Conclusions In this context of high HIV prevalence, significant progress has been achieved with regards to reaching the UNAIDS 90-90-90 targets. The third 90, viral suppression in people on ART, was achieved among women and men. However, gaps persist in HIV diagnosis and ART coverage particularly in men and individuals younger than 30 years. Achieving 90-90-90 is feasible but requires additional investment to reach youth and men.